Predictive value of the Kuijer score for bleeding and other adverse in-hospital events in patients with venous thromboembolism - Keller, Karsten; Münzel, Thomas; Hobohm, Lukas; Ostad, Mir A. (International journal of cardiology, 2021)
Background - Venous thromboembolism (VTE) constitute a major global burden of disease. Current international guidelines recommend treatment with anticoagulant therapy after VTE for a duration of at least 3 months. Since anticoagulation also imposes an increased risk for bleeding events, the individual risk has to be evaluated to determine adequate treatment plans. - Methods - The nationwide German inpatient sample of the years 2005-2017 was used for this analysis. Hospitalized VTE patients were stratified according to Kuijer risk class and the performance of the Kuijer score was evaluated to predict adverse in-hospital events. - Results - Overall, 1,204,895 VTE patients were treated between 2005 and 2017 in Germany and were included in the present study (839,143 patients had deep venous thrombosis and/or thrombophlebitis and 669,881 patients pulmonary embolism). According to Kuijer risk class stratification, in total, 176,723 (14.7%) of the hospitalized VTE patients were classified as low risk, 914,964 (75.9%) as intermediate risk and 113,208 (9.4%) as high risk. A higher Kuijer risk class was predictive for in-hospital death (odds ratio [OR] 1.99 [95% confidence interval (CI) 1.96-2.02], P < 0.001), major adverse cardiovascular and cerebrovascular events (MACCE, OR 1.90 [95%CI 1.87-1.93], P < 0.001), intracerebral bleeding (OR 1.28 [95%CI 1.14-1.44], P < 0.001), gastrointestinal bleeding (OR 1.56 [95%CI 1.48-1.64], P < 0.001) as well as necessity of transfusion of blood constituents (OR 2.94 [95%CI 2.88-3.00], P < 0.001) independently of important comorbidities. - Conclusions - The Kuijer score is an important risk stratification tool to predict individual risk regarding in-hospital outcomes comprising major bleeding events such as intracerebral bleeding and necessity of transfusion of blood constituents, but also in-hospital mortality and MACCE in VTE patients.